2019
DOI: 10.12688/aasopenres.12964.1
|View full text |Cite
|
Sign up to set email alerts
|

The quality of public sources of drinking water in oil-bearing communities in the Niger Delta region of Nigeria

Abstract: Background:Studies carried out in the Niger Delta region of Nigeria have demonstrated a link between oil exploration and poor-quality drinking water. However, many of these studies have been limited by small coverage and focus on few parameters. This study thus aimed at a comprehensive assessment of the quality of public sources of drinking water in three gas flaring and three non-gas flaring communities in the Niger Delta region of Nigeria.Methods:A total of 13 samples were collected from the major sources of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Ogbonna, Ekweozor and Igwe (2002) 2018reported that there is urgent need to ensure regular supply of potable water to the people in the oil producing communities of the Niger Delta because their right to water is being violated as they are compelled to drink polluted water. Maduka and Ephraim-Emmanuel (2019) reported that crude oil exploration and associated harmful activities such as oil spills and gas-flaring have adversely affected the health of the people and the biological, economic and socio-cultural life of the oil bearing communities in the Niger Delta. Adeola et al (2015) reported that drinking water sampled from water boreholes in Eliozu community, Rivers state were contaminated and he recommended regular monitoring of the physico-chemical properties of groundwater sources in Eliozu and other parts of the Niger Delta to ensure safe drinking water for the people.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ogbonna, Ekweozor and Igwe (2002) 2018reported that there is urgent need to ensure regular supply of potable water to the people in the oil producing communities of the Niger Delta because their right to water is being violated as they are compelled to drink polluted water. Maduka and Ephraim-Emmanuel (2019) reported that crude oil exploration and associated harmful activities such as oil spills and gas-flaring have adversely affected the health of the people and the biological, economic and socio-cultural life of the oil bearing communities in the Niger Delta. Adeola et al (2015) reported that drinking water sampled from water boreholes in Eliozu community, Rivers state were contaminated and he recommended regular monitoring of the physico-chemical properties of groundwater sources in Eliozu and other parts of the Niger Delta to ensure safe drinking water for the people.…”
Section: Resultsmentioning
confidence: 99%
“…Amnesty international (2018) reported that there is urgent need to ensure regular supply of potable water to the people in the oil producing communities of the Niger Delta because their right to water is being violated as they are compelled to drink polluted water. Maduka and Ephraim-Emmanuel (2019) reported that crude oil exploration and associated harmful activities such as oil spills and gas-flaring have adversely affected the health of the people and the biological, economic and socio-cultural life of the oil bearing communities in the Niger Delta. Adeola et al.…”
Section: Resultsmentioning
confidence: 99%
“…23, 24] There is need for major improvements in making domestic potable water available to the populace to attain the Sustainable Development Goals (SDGs) of improving water availability, accessibility, quality, and utilization study found surface water and water vendors to be the second most common source of water in non-oil-bearing and oil-bearing communities, respectively. This may be because oil exploration activities have been shown to pollute surface water resulting in a myriad of health problems [25][26][27] and environmental pollution There is need for the enforcement of the laws and penalties that protect the environment from pollution [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…13 In Nigeria, these environmentally deleterious activities such as deposition of industrial waste containing harmful petroleum effluents, gas flaring, and so on still go on despite having constitutional basis (eg, section 3 of the "Associated Gas Reinjection Act" of Nigeria) that makes them illegal. 14,15 Many PAHs possess the capacity to be carcinogenic, mutagenic, bioaccumulative, toxic, and persistent in the environment for long periods of time. They have thus come to be regarded as potentially harmful to the environmental and seen as a source of public health concern.…”
Section: Introductionmentioning
confidence: 99%